Dutch Reformed Church in inner city Pretoria: forming a new church space in South Africa: 1856–2020 - Mlambo, Ntandoyenkosi (Stellenbosch Theological Journal, 2024)
The Dutch Reformed Church in South Africa, over time, became a state church and aligned with the Apartheid regime and in some corners supported separate development. Moreover, the church would, working with colonial and apartheid cultural powers granted to it, gain numerous landholdings across South Africa. The Dutch Reformed Church property ownership, revealed in a 1998 inventory (which was said to be incomplete), sat at 600 properties and covering over fourteen thousand hectares. This article will discuss the church’s rise in the colony and in South Africa’s northern areas. It will also explain its historical landholding in South Africa in general as well as in the capital, Pretoria. Moreover, it will detail interviews with church leaders in a presbytery in Pretoria and explain learnings from history and spatial changes and what these may mean for the church at large.